A Comprehensive Systematic Review of Relationship between Coffee Consumption and The Risk of Calcium Oxalate Stone Formation - Wily Danis Pratama; Shavira Putri Pratama (The International Journal of Medical Science and Health Research, 2026)
Introduction: Kidney stones, particularly calcium oxalate stones, are a prevalent and painful urological condition with significant healthcare burdens. Dietary factors play a crucial role in their pathogenesis. Coffee, one of the world's most consumed beverages, contains various bioactive compounds, but its specific relationship with calcium oxalate stone risk remains a topic of scientific inquiry, with conflicting public perception. Methods: A systematic review methodology was employed. Thirteen sources, including cohort studies, meta-analyses, and a Mendelian randomization study, were identified through a structured screening process focusing on human adults, quantifiable coffee exposure, and calcium oxalate stone outcomes. Data were extracted on coffee consumption patterns, stone outcomes, risk associations, study populations, confounding adjustments, and proposed biological mechanisms. Results: The synthesized evidence consistently demonstrates a protective association between coffee consumption and kidney stone risk. Meta-analyses reported a significant risk reduction, with odds ratios (OR) of 0.70 (95% CI 0.60-0.82) for highest vs. lowest coffee intake and a relative risk (RR) of 0.68 (95% CI 0.61-0.75) for highest vs. lowest caffeine intake (Wang et al., 2014; Zhao et al., 2022). A Mendelian randomization study provided strong causal evidence, showing a 40% lower risk (OR=0.60, 95% CI 0.46-0.79) per 50% genetically predicted increase in coffee consumption (Yuan and Larsson, 2021). Proposed mechanisms include caffeine-induced diuresis increasing urine volume, increased excretion of citrate and magnesium, and direct inhibition of calcium oxalate crystal adhesion to renal cells (Barghouthy et al., 2020; Peerapen and Thongboonkerd, 2018). Discussion: The findings robustly indicate that moderate coffee consumption (typically 3-4 cups daily) is associated with a reduced risk of kidney stone formation. This effect is biologically plausible through multiple pathways involving both caffeine and other coffee compounds like chlorogenic acid and trigonelline. The consistency across diverse study designs, including genetically informed methods, strengthens causal inference. Limitations include the general focus on kidney stones overall rather than exclusively on calcium oxalate composition and the predominance of Western populations in the studies. Conclusion: Current evidence supports that coffee consumption is associated with a lower risk of kidney stone formation, including calcium oxalate stones. The protective effect is likely mediated through a combination of increased urine output, favorable changes in urinary composition, and direct anti-lithogenic actions. For most healthy adults, moderate coffee intake can be considered part of a dietary pattern that may mitigate stone risk. Future research should focus on stone-type-specific analyses and diverse populations.